Highly sensitive and selective fluorescent chemosensor for Ag+ based on a coumarin-Se2N chelating conjugate - Huang, Shanshan; He, Song; Lu, Yan; Wei, Fangfang; Zeng, Xianshun; Zhao, Liancheng (Chemical communications (Cambridge, England), 2011)
A highly sensitive and selective fluorescent chemosensor SC1 for Ag+ based on a coumarin-Se2N chelating conjugate has been synthesized and characterized. Due to inhibiting a photoinduced electron transfer (PET) quenching pathway, a fluorescent enhancement factor of 4-fold is observed under the binding of the Ag+ cation to the chemosensor SC1 with a detection limit down to the 10(-8) M range.